Are Geopolitical, Economy, and Social Affecting Unemployments? Evidence From ASEAN-5 - Danang Tri Hatmaja; Muhammad Khoirul Fuddin (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
East and Southeast Asia gain tremendous economic and political advantages in terms of economic geopolitics (GPE). However, the impact that emerged in the GPE was further exacerbated by the emergence of the covid pandemic,